2020
DOI: 10.36355/jas.v4i1.361
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Daya Saing Komoditas Kedelai Pada Lahan Kering Di Kabupaten Tebo

Abstract: Konsumsi kedelai nasional mengalami peningkatan setiap tahunnya sedangkan produksi kedelai nasional cendrung stagnan atau hanya mampu memenuhi 30 persen dari kebutuhan konsumsi kedelai nasional sehingga impor kedelai setiap tahunnya juga mengalami peningkatan.Penilitian ini bertujuan untuk melihat daya saing kedelai dan dampak kebijakan pemerintah terhadap daya saing kedelai pada lahan kering di Kabupaten Tebo.Penelitian ini menggunakan pendekatan Policy Analysis Matrix (PAM). Sumber data yang digunakan yaitu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar results can also be found in soybean farming in Wonogiri Regency (Sari & Prajanti, 2016). Similar results were also found for soybean farming in Tebo Regency, South Sulawesi (Kata, 2021). This means that soybean farming in Indonesia still has the potential to provide both economic and social benefits.…”
Section: The Financial and Economic Benefits Of Soybean Farming Businesssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results can also be found in soybean farming in Wonogiri Regency (Sari & Prajanti, 2016). Similar results were also found for soybean farming in Tebo Regency, South Sulawesi (Kata, 2021). This means that soybean farming in Indonesia still has the potential to provide both economic and social benefits.…”
Section: The Financial and Economic Benefits Of Soybean Farming Businesssupporting
confidence: 80%
“…Based on Table 9, it can be shown that the net transfer value is greater than zero (NT>0), indicating that there is an additional surplus for producers due to government policies applied to inputs and outputs simultaneously. Net transfer (NT) also describes whether government policies benefit or harm soybean farmers in Jember Regency (Kata, 2021). The analysis of net transfer (NT) for soybean commodities in Jember Regency obtained a negative value.…”
Section: Government Policies On Input and Outputmentioning
confidence: 99%
“…Soybean farming has no competitiveness if the output is sold for consumption in the market to tofu and tempeh factories. However, if the soybean agribusiness policy to increase competitiveness results in a change in consumption patterns by marketing soybeans as a source of vegetable protein that is safe for health, but also as a source of functional food, then soybeans have potential a strategic value to increase national food security in a sustainable, healthy, and educative manner [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuating prices of these feeds in West Papua are related to scarcity and competition. As we know that tofu waste is a by-product of the tempe and tofu manufacturing industry (Hidayat 2012;Kata et al 2020). The majority of the tofu industry uses imported soybeans as the raw material for making tofu, so the unstable price of this commodity will affect the price of its associated products as well.…”
Section: Regencymentioning
confidence: 99%